2011
DOI: 10.1007/s00296-011-1931-x
|View full text |Cite
|
Sign up to set email alerts
|

High Frequencies and co-existing of myositis-specific autoantibodies in patients with idiopathic inflammatory myopathies overlapped to rheumatoid arthritis

Abstract: A small proportion of patients with rheumatoid arthritis (RA) develop idiopathic inflammatory myopathies (IIM); however, the clinical and immunological characteristics of these patients have not been elucidated. In the present study, we evaluate the frequency of autoantibodies and the accompanying clinical features in patients with IIM overlapped to RA (IIM-RA) and in patients with IIM without RA. Twelve patients with IIM-RA were selected from 142 patients with IIM who were admitted to our hospital. Clinical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 15 publications
(23 reference statements)
0
16
0
1
Order By: Relevance
“…The coincidence of myopathies and RA has been previously described in case series of patients (7 cases of DM and RA, 16 cases of PM and RA, and 15 cases of unspecified DM or PM associated to RA). However, no uniform criteria or detailed case records can be found regarding these cases and only 8 completely described case reports with clear overlap between RA and DM/PM (Brunasso and Massone, 2011, Martínez—Cordero et al, 2001, Nagashima et al, 2009, Nakajima et al, 2012) can be found in the literature [2730]. Considering the rarity of the linkage between RA and inflammatory myopathies (DM/PM), most of the cases analyzed in the present study might not represent a sporadic association because of the history of introduction of an anti-TNF- α agent and the improvement after withdrawal of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…The coincidence of myopathies and RA has been previously described in case series of patients (7 cases of DM and RA, 16 cases of PM and RA, and 15 cases of unspecified DM or PM associated to RA). However, no uniform criteria or detailed case records can be found regarding these cases and only 8 completely described case reports with clear overlap between RA and DM/PM (Brunasso and Massone, 2011, Martínez—Cordero et al, 2001, Nagashima et al, 2009, Nakajima et al, 2012) can be found in the literature [2730]. Considering the rarity of the linkage between RA and inflammatory myopathies (DM/PM), most of the cases analyzed in the present study might not represent a sporadic association because of the history of introduction of an anti-TNF- α agent and the improvement after withdrawal of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…The MSAs include two classes of cytoplasmic antibodies: those directed against Mi-2 and Mas antigens and others targeting translational proteins such as various tRNA synthetases, the SRP, transcriptional intermediary factor-1 (TIF1;anti-155/140 Ab) and the melanoma differentiation-associated gene-5 (MDA5; anti-CADM140 Ab). 53 While most patients have no detectable MSAs and a rare case may have two detectable MSAs, 54, 55 those that have it carry mostly one MSA type in association with specific HLA haplotypes. 1, 56 …”
Section: Laboratory Studies In Dm Pm and Nmmentioning
confidence: 99%
“…16 Bernstein et al 6 have reported anti-Jo-1 antibodies in the sera of 25% of PM/DM patients, 7.5% of myositis patients without the complication of ILD, 68% of patients with ILD complication, and 3% of patients with ILD in the absence of myositis. In another study, anti-Jo-1 antibodies have also been reported in 15-30% of PM patients and 60-70% of ILD patients.…”
Section: Discussionmentioning
confidence: 99%